Institutions of Scientific Efficiency: Organizations of the Middle Urals - Vlasov, Maksim Vladislavovich; Popov, Evgeny Vasilyevich (Economy of Regions, 2017)
In the article, the authors show that the main institutions of scientific efficiency are the institutions that publish scientific articles in Russian and international journals as well as monographs, scientific conference abstracts, pre-prints, reviews, reports, and also the institutions that register patents. The purpose of the research is the development of the indicator for the evaluation of the dysfunction of the institutions of scientific efficiency depending on different types of transaction coasts; and verification of the authors’ indicator of scientific efficiency by the empirical study of the scientific organizations’ activities. In the research, we applied the methods of the system, logical and economic analysis. The empirical information was processed using the methods of statistical analysis and correlation analysis. On the basis of different scientific efficiency of the central and regional institutions confirmed by Scopus data, the authors have proved that the scientific efficiency of regional scientific institutions and central ones need to be analysed separately. We have determined the dysfunctions of these institutions depending on different types of transaction coasts. We have developed the indicator for the assessment of the dysfunction of scientific efficiency institutions depending on different types of transaction coasts. The authors have introduced the indicator of scientific efficiency equal to the ratio of the dynamics of the increment of scientific results to the dynamics of the increase of transaction coasts. Depending on a type of the analyzed transaction coasts, the indicator of scientific efficiency illustrates the efficiency of various economic institutions. On the basis of the analysis of the research findings of the middle Urals’ scientific organizations, we have arrived at the conclusion that the institutions that publish articles in the Russian and foreign scientific journals are efficient. We defined the dysfunctions of the institutions that publish articles in the Russian and foreign scientific journals depending on different types of transaction coasts. The authors conclude that it is efficient to increase certain types of transaction coasts. The received results can be applied by regional scientific institutions to increase the efficiency of their scientific activity.